Nonlinear optics of coupled nanophotonic reasonators - Banerjee, Rimi (Nanyang Technological University, 2021)
Excitons are bound hydrogen-like states of electrons and holes, typically appear- ing in semiconductor quantum wells. Their electric dipole moment allows them to couple with light in resonating structures (e.g. microcavities, micropillars, and microring resonators, etc.). In the strong coupling limit, they form hybrid states called exciton-polaritons. Being mixed states, exciton-polaritons adopt some properties from excitons and some properties from photons, such as: strong nonlinearity, sensitivity to electric/magnetic fields, light effective mass, long dephasing time, rich spin dynamics, etc. These astonishing properties make them suitable for spin-dependent devices and low-power ultrafast switching based optoelectronics devices. Besides, due to their effective mass they can also form Bose-Einstein condensates at relatively high temperatures, even at room temperature. This thesis concerns four different theoretical proposals in exciton-polariton systems. First, we introduce a scheme to obtain Hofstadter’s butterfly with polarization splitting, which generates an artificial gauge field in the system. This field breaks the time reversal symmetry in the system and enables us to achieve topologically protected one-way edge modes. Second, we study second-order topological modes in exciton-polariton square lattice. In particular, we propose coupling of topological corner modes with the help of nonlinearity to achieve robust memory- based devices as well as communication between them via edge states. Third, we propose theoretically a feedback-free optical spin filter in a honeycomb lattice geometry, where the system allows only one of the pure spins in the system to propagate along one of the edges, while propagation in the opposite direction is restricted even considering the opposite edge. In the considered system all the edge states split in energy and there exists an energy window where one edge state has a pure spin and is surrounded by bulk states of opposite spin, which enable propagation of spin unhampered even in a remarkably thin strip. Fourth, we introduce a theoretical scheme for cellular automatons (CAs) in the exciton- polariton system, which automatically gives rise to a variety of solitons. Due to the Turing completeness of the CAs, this scheme will be able to reproduce arbitrary logic circuits.